Chlorinated Cubane-1,4-dicarboxylic Acids - Křížková, Adéla; Bastien, Guillaume; Rončević, Igor; Císařová, Ivana; Rybáček, Jiří; Kašička, Václav; Kaleta, Jiří (The Journal of organic chemistry, 2024)
Herein, we report radical chlorination of cubane-1,4-dicarboxylic acid leading preferentially to one monochlorinated cubane dicarboxylate (ca. 70%) that is accompanied by four dichlorinated derivatives (ca. 20% in total). The exact positions of the chlorine atoms have been confirmed by X-ray diffraction of the corresponding single crystals. The acidity constants of all dicarboxylic acids in water were determined by capillary electrophoresis (3.17 ± 0.04 and 4.09 ± 0.05 for monochlorinated and ca. 2.71 ± 0.05 and 3.75 ± 0.05 for dichlorinated cubanes). All chlorinated derivatives as well as the parent diacid showed high thermal stability (decomposition above 250 °C) as documented by differential scanning calorimetry. The probable reaction pathways leading to individual isomers were proposed, and the energies of individual transition states and intermediates were obtained using density functional theory calculations (B3LYP-D3BJ/6-311+G(d,p)). The relative strain energies for all newly prepared derivatives as well as for hypothetical hexahalogenated (fluorinated, chlorinated, brominated, and iodinated) derivatives of cubane-1,4-dicarboxylic acids were predicted using wavefunction theory methods. The hexafluorinated derivative was identified as the most strained compound (57.5 kcal/mol), and the relative strain decreased as the size of halogen atoms increased (23.7 for hexachloro, 16.7 for hexabromo, and 4.0 kcal/mol for the hexaiodo derivative).